Evaluation of sampling methods for Bacillus spore-contaminated HVAC filters - Calfee, M. Worth; Rose, Laura J.; Tufts, Jenia; Morse, Stephen; Clayton, Matt; Touati, Abderrahmane; Griffin-Gatchalian, Nicole; Slone, Christina; McSweeney, Neal (Journal of microbiological methods, 2014)
The objective of this study was to compare an extraction-based sampling method to two vacuum-based sampling methods (vacuum sock and 37mm cassette filter) with regards to their ability to recover Bacillus atrophaeus spores (surrogate for Bacillus anthracis) from pleated heating, ventilation, and air conditioning (HVAC) filters that are typically found in commercial and residential buildings. Electrostatic and mechanical HVAC filters were tested, both without and after loading with dust to 50% of their total holding capacity. The results were analyzed by one-way ANOVA across material types, presence or absence of dust, and sampling device. The extraction method gave higher relative recoveries than the two vacuum methods evaluated (p≤0.001). On average, recoveries obtained by the vacuum methods were about 30% of those achieved by the extraction method. Relative recoveries between the two vacuum methods were not significantly different (p>0.05). Although extraction methods yielded higher recoveries than vacuum methods, either HVAC filter sampling approach may provide a rapid and inexpensive mechanism for understanding the extent of contamination following a wide-area biological release incident. •Spore recovery from neat and dust-loaded HVAC filters was determined.•Vacuum- and extraction-based methods were compared.•Neither the filter type nor the presence of dust significantly affected recovery.•Recoveries by vacuum methods were typically 30% of those by extraction.•Results may guide selection of sampling methods following a biological incident.